Compulsive sexual behavior, sexual functioning problems, and their linkages to substance use among German medical students: exploring the role of sex and trauma exposure - Jepsen, Dennis; Luck, Tobias; Heckel, Christian; Niemann, Jana; Winter, Kristina; Watzke, Stefan (Frontiers in Psychology, 2024)
Sexual problems relevant to psychotherapy, such as compulsive sexual behavior (CSB) and sexual functioning problems (SFP), have been related to harmful substance use in several studies. Substance use is prevalent among medical students (MS) and is often considered a maladaptive coping strategy for stress, as well as a risk factor for mental health issues. Sexual problems and substance use share trauma exposure and post-traumatic symptoms as risk factors for their development. This study aimed to explore the interaction effects between problematic sexual behaviors, substance use, and trauma among German MS. A cross-sectional study (n = 359; 69% women, 29% men) was conducted using an online questionnaire. MS at a German university were recruited via email. CSB (CSBD-19), SFP (SBQ), harmful alcohol (AUDIT) and drug use (DAST), childhood trauma exposure (CTQ), and current post-traumatic symptoms (IES-R) were assessed. Multivariate linear and ordinal regressions, as well as path analyses, were conducted to investigate associations between the study variables. CSB was identified in 3% of all MS. The most commonly reported SFPs were decreased sexual desire and difficulties achieving orgasms among women and premature ejaculation among men. Higher CSBD scores were predicted by male sex, elevated AUDIT scores, and increased frequencies of hyperarousal (IES-R). Path analyses revealed associations between the severity of emotional/sexual abuse, the intensity of post-traumatic symptoms, and both CSBD and AUDIT scores. Among female MS, less severe emotional abuse and more severe physical abuse in childhood predicted higher frequencies of orgasmic difficulties. The frequency of SFPs was correlated with the use of benzodiazepines among female MS, with cannabis and MDMA/ecstasy among male MS, and with cocaine/crack, speed, and AUDIT among both sexes. No interaction effects were found between SFPs, substance use, or trauma-related factors in the path analyses. To some extent, there appears to be a relationship between substance use, childhood trauma exposure, and currently persisting post-traumatic symptoms with problematic sexual behaviors among MS. However, further research is required to explore these relationships in greater depth and to identify the underlying pathways. Mental health support measures should incorporate the factors of sexuality, substance use, and trauma while also exploring their relationships with workload, career-related anxieties, and other curriculum-related factors.